Perbaikan User Interface Website Badan Narkotika Nasional Provinsi Jawa Timur Menggunakan Pendekatan Human-Centered Design - Windha Parwaningsuci; Hanifah Muslimah Az-Zahra; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Badan Narkotika Nasional (BNN) East Java Province published website for the aim of sharing information and conducting communication with the society, especially in East Java Province region. On current time, website-based communication has became an urgency for the institutions due to large number of narcotics misuse in Indonesian society. This research is focused on evaluation and improvement of the institution's website in user interface aspect by using Human-Centered Design (HCD) approach. HCD is used for developing interactive systems with the aim to make the system usable and useful. This research applies the principle of process customization, ie the stages of HCD will be adjusted based on the current condition of the website. The research is started with context of use analysis, initial design evaluation, user's requirement analysis, solution design production, and solution design evaluation. The result of the research has shown that after the application of HCD method, the user interface has a better usability value than before the implementation of the HCD method. The usability value of efectivity aspect in initial design is 45.71%, while the value is increased to 100% on solution design. On the efficiency aspect, usability value in initial design is 46.20% and in solution design is increased to 100%. Average time to done all tasks in solution design is decreased compared to initial design. In the aspect of user satisfaction, the percentage of user satisfication in initial design is 40.75% and in solution design is increased to 81.75%.